2004
DOI: 10.1111/j.1365-2222.2004.01896.x
|View full text |Cite
|
Sign up to set email alerts
|

Low numbers of interleukin‐12‐producing cord blood mononuclear cells and immunoglobulin E sensitization in early childhood

Abstract: Although the numbers of infants in our study are limited our data suggest that a low number of IL-12-producing CBMC is associated with IgE sensitization during early childhood and that a reduced number of IFN-gamma-producing CBMC promotes the development of AEDS during the first 2 years of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
1
23
1
1
Order By: Relevance
“…an increased interleukin (IL)-4 to interferon (IFN)-γ ratio and lower numbers of IL-12-producing cells than CBMC obtained from children born to non-atopic mothers [2]. In a follow-up study, when the same children were evaluated on basis of their immunoglobulin E (IgE)-sensitization status at the age of 2 years, our data revealed that there was no correlation between an increased cord blood IL-4 : IFN-γ ratio and the development of early atopy [3]. Rather, our data showed that children developing early IgE-sensitization had fewer IL-12-producing CBMC compared to their non-sensitized counterparts.…”
Section: Introductionmentioning
confidence: 61%
“…an increased interleukin (IL)-4 to interferon (IFN)-γ ratio and lower numbers of IL-12-producing cells than CBMC obtained from children born to non-atopic mothers [2]. In a follow-up study, when the same children were evaluated on basis of their immunoglobulin E (IgE)-sensitization status at the age of 2 years, our data revealed that there was no correlation between an increased cord blood IL-4 : IFN-γ ratio and the development of early atopy [3]. Rather, our data showed that children developing early IgE-sensitization had fewer IL-12-producing CBMC compared to their non-sensitized counterparts.…”
Section: Introductionmentioning
confidence: 61%
“…This Th2 bias is usually considered to be a major underlying mechanism for the development of atopy in early life, and could again be a consequence of APC defects. Supporting this concept, low numbers of IL-12-producing cells have been observed in neonates with inherited atopic disease [88,89], as well as low LPS-induced production of IL-12 in children who develop atopic diseases compared to children who do not [90]. The baseline expression of HLA Class II on CB monocytes is lower in children in whom allergic diseases developed within the first two years of life [91].…”
Section: The Immune Response In Early Childhood Yearsmentioning
confidence: 94%
“…and IFN-γ-producing CBMCs and lower IFN-γ secretion after allergen stimulation have been associated with development of allergic symptoms and sensitisation later in life [174,175,201]. The discrepant immune response at birth, might be associated with exposure to a strong Th2 environment in utero.…”
Section: Postnatal Development Of the Immune Systemmentioning
confidence: 99%